2020
DOI: 10.18103/mra.v8i5.2096
|View full text |Cite
|
Sign up to set email alerts
|

Dysthrophic calcification in Systemic Sclerosis – Intralesional Injections of Sodium Thiosulfate may have significant Positive Effects on your patients

Abstract: To describe our three year experience with intralesional injection of sodium thiosulfate (STS) as treatment for dystrophic calcification (DC) in patients suffering from systemic sclerosis (SSc), overlap syndrome, or dermatomyositis. Methods: Between September 2016 and October 2019, selected SSc, overlap syndrome, and dermatomyositis patients with problematic DC were systematically and prospectively recruited to treatment once a week for four weeks and follow up after 12-16 weeks. During each visit, data concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“… Er:YAG erbium-doped yttrium aluminium garnet, ESWL extracorporeal shockwave lithotripsy, N/A not applicable, N/R not reported, STS sodium thiosulfate a Missing data were managed by available case analysis and mean imputation was used when a mean was known for a variable of interest but exact values were not reported for individual cases from a single study b Olesen et al [ 17 ] also reported injection pain, however, without an exact number of cases experiencing it c A group of patients was too small d Bottomley et al [ 13 ] reported outcomes as for particular lesions instead of describing overall response in each patient …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Er:YAG erbium-doped yttrium aluminium garnet, ESWL extracorporeal shockwave lithotripsy, N/A not applicable, N/R not reported, STS sodium thiosulfate a Missing data were managed by available case analysis and mean imputation was used when a mean was known for a variable of interest but exact values were not reported for individual cases from a single study b Olesen et al [ 17 ] also reported injection pain, however, without an exact number of cases experiencing it c A group of patients was too small d Bottomley et al [ 13 ] reported outcomes as for particular lesions instead of describing overall response in each patient …”
Section: Resultsmentioning
confidence: 99%
“…A total of 410 articles were retrieved from the search. Additionally, ten more studies were added after the manual screening of the reference sections [10,[17][18][19][20][21][22][23][24][25]. Eight articles were excluded at the eligibility stage due to reporting patients described in other included studies [20,26,27] or insufficient data [24,25,[28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations